Neuroprotection and spatial memory enhancement of four herbal mixture extract in HT22 hippocampal cells and a mouse model of focal cerebral ischemia. Issue 1 (December 2015) - Ahn, Sung; Kim, Yu; Kim, Ha; Choi, Young; Lee, Jae; Kim, Cheol; Baek, Jin; Shin, Hwa; Choi, Byung
Abstract Background Four traditional Korean medicinal herbs which act in retarding the aging process, Polygonum multiflorum Thunb., Rehmannia glutinosa (Gaertn) Libosch., Polygala tenuifolia Willd., andAcorus gramineus Soland., were prepared by systematic investigation of Dongeuibogam (Treasured Mirror of Eastern Medicine), published in the early 17th century in Korea. This study was performed to evaluate beneficial effects of four herbal mixture extract (PMC-12) on hippocampal neuron and spatial memory. Methods High performance liquid chromatography (HPLC) analysis was performed for standardization of PMC-12. Cell viability, lactate dehydrogenase, flow cytometry, reactive oxygen species (ROS), and Western blot assays were performed in HT22 hippocampal cells and immunohistochemistry and behavioral tests were performed in a mouse model of focal cerebral ischemia in order to observe alterations of hippocampal cell survival and subsequent memory function. Results In the HPLC analysis, PMC-12 was standardized to contain 3.09 % 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-D-glucoside, 0.35 % 3′, 6-disinapoyl sucrose, and 0.79 % catalpol. In HT22 cells, pretreatment with PMC-12 resulted in significantly reduced glutamate-induced apoptotic cell death. Pretreatment with PMC-12 also resulted in suppression of ROS accumulation in connection with cellular Ca2+ level after exposure to glutamate. Expression levels of phosphorylated p38 mitogen-activated protein kinases (MAPK) and dephosphorylated phosphatidylinositol-3 kinase (PI3K) by glutamate exposure were recovered by pretreatment with either PMC-12 or anti-oxidant N-acetyl-L-cysteine (NAC). Expression levels of mature brain-derived neurotrophic factor (BDNF) and phosphorylated cAMP response element binding protein (CREB) were significantly enhanced by treatment with either PMC-12 or NAC. Combination treatment with PMC-12, NAC, and intracellular Ca2+ inhibitor BAPTA showed similar expression levels. In a mouse model of focal cerebral ischemia, we observed higher expression of mature BDNF and phosphorylation of CREB in the hippocampus and further confirmed improved spatial memory by treatment with PMC-12. Conclusions Our results suggest that PMC-12 mainly exerted protective effects on hippocampal neurons through suppression of Ca2+ -related ROS accumulation and regulation of signaling pathways of p38 MAPK and PI3K associated with mature BDNF expression and CREB phosphorylation and subsequently enhanced spatial memory.